Experimental investigation of hardness of FSW and TIG joints of Aluminium alloys of AA7075 and AA6061 - Chetan Patil; Hemant Patil; Hiralal Patil (Fracture and Structural Integrity)
This paper reports hardness testing conducted on welded butt joints by FSW and TIG welding process on similar and dissimilar aluminium alloys. FSW joints were produced for similar alloys of AA7075T651 and dissimilar alloys of AA7075T651- AA6061T6. The Friction stir welds of AA7075 & AA6061 aluminium alloy were produced at different tool rotational speeds of 650,700, 800, 900, 1000 and transverse speed of 30, 35, 40 mm/min. TIG welding was conducted along the rolling direction of similar and dissimilar aluminium plates. The Brinell hardness testing techniques were employed to conduct the tests; these tests were conducted on the welds to ascertain the joint integrity before characterization to have an idea of the quality of the welds